Defective hMSH2/hMLH1 protein expression is seen infrequently in ulcerative colitis associated colorectal cancers. Issue 3 (1st March 2000) - Cawkwell, L; Sutherland, F; Murgatroyd, H; Jarvis, P; Gray, S; Cross, D; Shepherd, N; Day, D; Quirke, P
Abstract : BACKGROUND: Ulcerative colitis is associated with an increased risk of colorectal cancer above that of the normal population. The relative risk correlates with the extent and duration of the disease but the genetic basis of ulcerative colitis associated cancer risk is not known. AIMS: To assess the prevalence of microsatellite instability and mismatch repair gene abnormalities in ulcerative colitis associated colorectal cancer. PATIENTS: Forty six patients with colorectal cancer, with a previous histological diagnosis of ulcerative colitis. METHODS: The frequency of microsatellite instability and/or immunohistochemical expression of hMSH2 and hMLH1 was assessed. Thirty three cases were investigated using both approaches. RESULTS: Although 6/41 (14.6%) cases showed microsatellite instability at one or more markers, only one case (2.4%) exhibited high level instability (at least two markers affected). Of 38 cases which were assessed using antibodies against hMSH2 and hMLH1, only one case (2.6%) showed loss of expression. This case, which showed loss of hMSH2 expression, was the same case which exhibited high level microsatellite instability. The 33 cases which were investigated using both approaches showed that loss of expression of either hMSH2 or hMLH1 was not seen in any case which exhibited microsatellite instability in no more than one marker. CONCLUSIONS: This study suggests that both high level microsatellite instability and loss of expression of hMSH2/hMLH1 are infrequent events in ulcerative colitis associated colorectal cancers. Low level microsatellite instability was not associated with loss of expression of either hMSH2 or hMLH1.